The Science of God : an introduction to scientific theology - McGrath, Alister E. (London : T & T Clark International, 2004)
This book is a clear, concise guide to Alister McGrath's groundbreaking three-volume work A scientific theology. McGrath himself here summarizes his major project and sketches out its implications for many aspects of Christian doctrine. He then explores all of the major themes of his three-volume work, including the legitimacy of a scientific theology, the purpose and place of natural theology, the foundations of theological realism, the failure of classic foundationalism, the nature of revelation, and the place of metaphysics in theology.
Includes index.
Keywords: Theology, Doctrinal; Natural theology; Scientific theology